Testicular Arteriovenous Malformation: Gray-Scale and Color Doppler Ultrasonography Features - Fatih Gulsen; Ismail Mihmanli; Fatih Kantarci; Abdulkadir Eren; Suleyman Onder Ataus (Case Reports in Medicine)
Intratesticular arteriovenous malformations (AVMs) are extremely rare benign incidental lesions of the testis. Ultrasonography (US) generally reveals a hypoechoic solid mass within the testicular parenchyma. We describe a patient with intratesticular AVM which was found incidentally during workup for infertility. The gray-scale and Doppler US appearance of an intratesticular AVM and the differential diagnosis have been presented. Based on the gray-scale, US appearance differentiation from malignant testicular tumors is difficult. Doppler US examination aids in the diagnosis by demonstrating the vascular nature of the tumor.